Endoscope assisted removal of impacted third molars from the lower mandibular border via lingual access - A. Gupta; K. Ganesan; T. Nagpal; V. Bhatt (Elsevier, 2023)
Purpose: Endoscopes are increasing the surgical spectrum for Oral and Maxillofacial Surgery. Naaj et al. quote that for third molars below the inferior dentoalveolar nerve (IDN), extra-oral removal is the best technique. The authors demonstrate that with endoscopic assistance, deeply impacted third molars can be removed intra-orally instead, without any complications. Endoscopes have demonstrated their usefulness in Oral and Maxillofacial surgery by aiding intra-oral repair of condylar fractures and submandibular gland removal; surgeries that are traditionally carried out with extra-oral access. The authors demonstrate how endoscopes have a place in minor oral surgery, particularly reducing the amount of bone removal needed to gain access to the surgical site. Methods: The article reports on two case studies of lingually placed third molars lying below the IDN. They were removed with endoscope assisted lingual access. Surgical planning was done using CT/CBCT scanning. The authors also detail how neurosensory disturbance was avoided when raising a lingual flap. Results: Wisdom teeth were successfully removed in all instances, whole, via lingual access. Patients had uneventful recovery and there were no cases of reported neurosensory disturbance. Conclusion: The authors demonstrate that the use of an endoscope, CT/CBCT guided surgical planning and careful lingual retraction provides a safe alternative to extra-oral removal of deeply impacted third molars. The advantages are avoidance of post-operative scarring and the potential to operate in ambulatory care.